A preliminary contribution to the petrography of the polished stone tools of Croatia - Burić, Marcel (Array, 2004)
This paper presents some preliminary data on the petrography of the polished stone tools from several Neolithic sites of Eastern Croatia and the Dalmatian Coast. They indicate that sandstone is the material more commonly used for tools manufacture. Although these data do not allow any definitive conclusion about the origin of the raw material employed, we can argue that most of them are of local origin, except for some nephrite instruments, which were undoubtedly imported.